Experiments on thermally driven internal water waves and their detectability with infrared surface thermography - Miklos Vincze; Zsolt Áron Kiss; Nóra Fenyvesi; Erzsébet Illés-Almár (Discover Applied Sciences, 2025)
Abstract In a simplified laboratory model of a stratified ocean basin with colder and warmer water layers we investigate the propagation of gravity currents, internal solitary waves, and solibores excited along the pycnocline. The dynamics of these disturbances are observed with a thermal camera mounted above the free water surface – imitating infrared satellite-based remote sensing – and with a visible range camera from the side simultaneously, to provide “ground truth” information on the nonlinear waves via dye tracing for the validation of the method. Contrasting the large-scale temporal changes of the surface temperature field and the internal wave propagation we find that, despite the fact that the interface (pycnocline) is orders of magnitude deeper than the penetration depth of the observed infrared radiation, certain surface signatures of the interfacial wave dynamics can be detected in the water surface temperature fields due to secondary convective flows. Such a coupling may be applicable for the exploration of internal waves using infrared sea-surface temperature data from satellites.